Keunggulan kaedah elektik sistematik dalam pengajaran dan pembelajaran Bahasa Arab kepada pelajar Melayu - Hj Maimun Aqsha Lubis, (Penerbit Universiti Kebangsaan Malaysia, 2009)
This study was conducted to compare the effectiveness of three methods of teaching the Arabic language namely the Taqlidiyah, the al-Sam’iyat al-Safawi’yah and the Eclectic Systematic. The purpose of this study was to determine which of the three methods was more effective in achieving proÞciency in the four language skill (listening, speaking, reading, and writing). The study was carried out using a quasi experimental design. Six groups of 50 students each from the matriculation centre of the International Islamic University were used as sample for this study. The Taqlidiyah method used some techniques of TAFL (Teaching Arabic As First Language), the al-Sam’iyat al-Shafawiyah method used some of the techniques of TASL (Teaching Arabic As A second Language). While the Eclectic Systematic method used the combination techniques of Taqlidiyah and al-Sam’iyat al-Safawi’yah method. The curriculum for six groups of students used in this study were controlled in terms of gender, nationality, basic Arabic language skills and Arabic language training outside classrooms. This study has identiÞed the characteristics and the procedures of the Eclectic Systematic teaching method, which was found suitable for the teaching of Arabic language for Malay student at the matriculation of the International Islamic University. Results of the study showed that the Taqlidiyah method was effective in teaching reading comprehension and writing skill for both the elementary and intermediate levels. The al-Sam’iyat al-Shafawiyah method was effective in teaching listening comprehension and speaking skill for both the elementary and intermediate levels. The Eclectic Systematic method was effective in teaching all four language skills for both the elementary and intermediate levels